2019
DOI: 10.1002/dac.4238
|View full text |Cite
|
Sign up to set email alerts
|

FRAME routing with game theory optimization for wireless networks

Abstract: Summary Wireless ad hoc networks have a wide variety of applications in the present world. Creating routes between the nodes and with low energy consumption is a major challenge in wireless ad hoc networks. In this paper, we have proposed FRAME routing for ad hoc networks, which consider the entire network based on hierarchal Bayesian model. It works on game theory–based Chow‐Liu algorithm for establishing routes from source to destination considering the best neighbors in the path. FRAME routing is further an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Subramanyam et al 36 suggested frame routing for ad hoc networks based on a hybrid Bayesian model. The related concept and Chow Liu algorithm and its pseudo code were explained to select the best neighbors from every node in the path from source to destination to reduce energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Subramanyam et al 36 suggested frame routing for ad hoc networks based on a hybrid Bayesian model. The related concept and Chow Liu algorithm and its pseudo code were explained to select the best neighbors from every node in the path from source to destination to reduce energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Many scholars have done a lot of research on it. Radha et al proposed a game theory optimization routing framework for wireless networks, which provided a solution for the realization of low-energy routing [7]. Zhu and Basar explored the game mechanism of the optimal cross-layer flexible control system to enhance the robustness and security of the cyber-physical system [8].…”
Section: Related Workmentioning
confidence: 99%
“…Even though there is no probability to win the champion, he will choose to be aggressive). Starting from relatively simple cases, this article assumes that only players at the top two board have theoretical hopes of winning the championship and investigate a four-player model, in which the players are with equal strength [10].…”
Section: Introductionmentioning
confidence: 99%